On the electrocatalytical oxygen reduction reaction activity and stability of quaternary RhMo-doped PtNi/C octahedral nanocrystals - Hornberger, Elisabeth; Klingenhof, Malte; Polani, Shlomi; Paciok, Paul; Kormanyos, Attila; Chattot, Raphael; Macarthur, Katherine E.; Wang, Xingli; Pan, Lujin; Drnec, Jakub; Cherevko, Serhiy; Heggen, Marc; et al. (Chemical Science, 2022)
Recently proposed bimetallic octahedral Pt-Ni electrocatalysts for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cell (PEMFC) cathodes suffer from particle instabilities in the form of Ni corrosion and shape degradation. Advanced trimetallic Pt-based electrocatalysts have contributed to their catalytic performance and stability. In this work, we propose and analyse a novel quaternary octahedral (oh-)Pt nanoalloy concept with two distinct metals serving as stabilizing surface dopants. An efficient solvothermal one-pot strategy was developed for the preparation of shape-controlled oh-PtNi catalysts doped with Rh and Mo in its surface. The as-prepared quaternary octahedral PtNi(RhMo) catalysts showed exceptionally high ORR performance accompanied by improved activity and shape integrity after stability tests compared to previously reported bi- and tri-metallic systems. Synthesis, performance characteristics and degradation behaviour are investigated targeting deeper understanding for catalyst system improvement strategies. A number of different operando and on-line analysis techniques were employed to monitor the structural and elemental evolution, including identical location scanning transmission electron microscopy and energy dispersive X-ray analysis (IL-STEM-EDX), operando wide angle X-ray spectroscopy (WAXS), and on-line scanning flow cell inductively coupled plasma mass spectrometry (SFC-ICP-MS). Our studies show that doping PtNi octahedral catalysts with small amounts of Rh and Mo suppresses detrimental Pt diffusion and thus offers an attractive new family of shaped Pt alloy catalysts for deployment in PEMFC cathode layers.
CRIS-Team Scopus Importer:2022-08-19